The Effect of Conjugated Linoleic Acid supplementation on the Serum Leptin Level, Pulmonary Function and Quality of Life in COPD Patients - Hasan Ghobadi (Journal of Ardabil University of Medical Sciences, 2019)
Background & objectives: Chronic Obstructive Pulmonary Disease (COPD) is accompanied by systemic inflammations and is characterized by irreversible airflow limitations. Leptin is a cytokine with pre-inflammatory effect. However, there have been no studies on the effect of conjugated linoleic acid (CLA) on the serum leptin concentration in COPD patients. Therefore, the present study aimed to explore the effect of CLA on the serum leptin level, lung function and quality of life in COPD patients. Methods: This interventional study was conducted on 90 COPD patients. The patients were randomly divided into two groups (supplement and placebo) with 45 patients per group. After obtaining written consent from the patients and recording their demographic characteristics, the spirometry was performed and COPD assessment test (CAT) score was calculated. Moreover, a fasting blood sample was collected from each of them in order to analyze their serum leptin concentration. After that, the patients in the supplement group were administered with 3.2 g/day of CLA for 6 weeks. The patients in another group received placebo. After the intervention, spirometry, CAT score calculation and blood sampling were repeated for all of the patients and the obtained results were analyzed. Results: after the intervention, a significant decrease both in the serum leptin level and in CAT score as a quality life marker  was observed in the supplement group (p<0.05). Moreover, the FEV1 levels as a lung function test, increased significantly in the supplement group after the intervention (p<0.05). Although, the difference between the two groups was not significant. Conclusion: The use of CLA supplement can improve COPD patients’ quality of life through decreasing the serum level of leptin in their blood.